Regional Paleo Climate Simulation over Eastern Mediterranean and the Nile River Basin with COSMO-CLM - Zhang, Mingyue; Justus Liebig University Giessen (My University, 2023)
The complex interaction between climate variability, extreme events, and societal dynamics within the Eastern Mediterranean (EM) and Nile River (NR) basin (EMNR) has captivated scholarly attention for years. Despite the importance of climate's influence on societies, most of the research primarily relied on proxy records, with limited attention to the detailed/regional/local information provided by Regional Climate Model (RCM) simulations. The primary objective of this study is to increase the understanding of regional and local climatic patterns within the EM and NR basin over two millennia based on a regional climate model - COSMO-CLM. This study highlights the necessity of bridging the gap of the coarse GCM resolution by employing RCMs, focusing on the paleo climate simulation over EM and NR region with COSMO-CLM (COnsortium for Small-scale MOdelling in CLimate Mode) model. More specifically, the first part of this thesis provides a sensitivity analysis of different land cover schemes in convective-permitting simulations within COSMO-CLM. Key among the external forcings is land use change, which significantly alters land surface properties affecting energy, water, and momentum exchanges between the land and atmosphere. By analyzing the simulated air temperature, the leaf area index and the plant coverage, this study underscored the need to carefully select appropriate Land Cover (LC) maps for regional climate modeling, as LC maps and fractions had substantial impacts on simulated air temperature, Leaf Area Index (LAI), and plant coverage. The study also indicated that analyzing the effects of heterogeneous land cover types on seasonal climate, as well as assessing the role of land cover in regional climate modeling, would be crucial for future research. Further investigations are also required to understand how regional climate responds to varying land cover distributions. The second part involves developing a transient paleo climate simulation for the past 2000 years using the COSMO-CLM model with its enhanced horizontal resolution up to 50 x 50 km, which incorporates several external forcings (solar, orbital, volcanic, greenhouse gases and land use change) to make the paleo simulations more realistic and more independent. By implementing those external forcings into COSMO-CLM, the study provides a dataset characterized by enhanced spatial (50 km) and temporal (monthly to hourly depending on the output variables) resolution. This approach can not only enable a comparative analysis between simulation outputs and proxy data but also foster the possibility of a comprehensive understanding of historical socio-climatic conditions. The research further compares the mean climate condition of EMNR between the ERP (Early Rome Period: 400-362 BCE) and PI (Pre-Industrial: 1800 -1850 CE), further, offering insights into large-scale circulation processes and their impact on regional climate conditions between ERP and PI. The results show that the mean climate conditions of the two selected periods are similar in terms of annual cycle but with increased variability from ERP to PI. In addition, the relationship between large-scale circulation features to regional temperature/precipitation patterns reveals stable large-scale circulation influence during both ERP and PI periods.
Keywords: Regional paleoclimate simulation; ddc:910